Pemberdayaan Ekonomi Petani Singkong Desa Tanjung Seteko melalui Diversifikasi Produk Keripik Singkong - Rosa Amelia; Reta Pajar Sari; Intan Ramandani; Indah Aulia Putri; Lora Malika Pradita; Vina Nabila; Muhammad Lutfhi Abdul Rahman; Gintan Rembige Lantax; Dessy Adriani; Erni Purbiyanti; Nurilla Elysa Putri; M. Huanza Huanza; Maulidia Tri Yuliani (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
The village of Tanjung Seteko, situated in Ogan Ilir District, has significant potential for cassava production; however, farmers in the village face challenges, including low selling prices. This is due to their continued dependence on middlemen and a lack of product processing. The goal of this empowerment program is to increase farmers' incomes by diversifying products through the processing of cassava into chips, which have better selling prices and wider market access. This program was implemented with the active participation of farmers and housewives, using the Participatory Action Research (PAR) method. The results of this activity show a change in the participants' perspective, from previously only selling raw Cassava, which has low economic value to individuals, can be leveraged to provide higher profits and open up opportunities for sustainable home businesses.